Growth in height and its association with overweight and obesity in Mexican children: an evaluation based on a nationally representative sample (ENSANUT 2018) - Flores, Luis Alberto; Datta Banik, Sudip; Cameron, Noel; Fragoso, Isabel Januário (Frontiers in Public Health, 2024)
The present study aimed to estimate the height growth curve for Mexican boys and girls based on their body mass index (BMI) status (normal and overweight/obese) and to develop a height Lambda, Mu, and Sigma (LMS) growth reference for Mexican children aged 2 to 18 years. Methods Chronological age and height records (7,097 boys and 6,167 girls) were obtained from the Mexican National Survey of Health and Nutrition database. Height growth curves were fitted using the Preece-Baines 1 (PB1) model and the LMS method. Results Age at peak height velocity (APHV) was 12.4 and 12.7 years for overweight-obese and normal-weight boys, respectively, and was 9.6 and 10.4 years for overweight-obese and normal-weight girls, respectively. Growth velocity was higher at the age of take-off (TO) in overweight-obese children than in normal-weight children (5.2 cm/year vs. 5 cm/year in boys and 6.1 cm/year vs. 5.6 cm/year in girls); nevertheless, the growth velocity at APHV was higher for normal-weight children than for overweight-obese children (7.4 cm/year vs. 6.6 cm/year in boys and 6.8 cm/year vs. 6.6 cm/year in girls, respectively). Distance curves developed in the present study and by the World Health Organization (WHO) using LMS showed similar values for L and S parameters and a higher M value compared with the WHO reference values. Conclusion This study concluded that overweight-obese children had earlier APHV and lower PHV than normal-weight children. Furthermore, Mexican children and adolescents were shorter than the WHO growth reference by age and sex.